Nilai Keterbukaan Ideologi Partai Islam dalam Perspektif Komunikasi Politik - Erfina Nurussa'adah (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2018)
The Prosperous and Justice Party or Partai Keadilan Sejahtera (PKS) is one of the parties different from a political party most, and more than that it can be seen that PKS is coming from the Muslim community in Indonesia. In the current development of Indonesian political parties, there is an impression that ideology of Indonesian political partis are moving to the middle. PKS has choosen to be an open political party or it can understood PKS is now determined to be one of the pluralistic parties who adopt pluralism and the diversity. This research wants to examine the value behind an opened ideology by Regional Council (DPW) of PKS in West Java in political communication perspective. Qualitative approach is used with ethnographic sudy. Data are collected by observations, interviews and documentary study on the internal and external informants of PKS. The result shows that opened ideology of DPW PKS of West Java are based on three values: ideological value, sociological value, and political value.